METROLOGICAL ANALYSIS OF DIFFERENT TECHNIQUES FOR MEASURING INTERFACE TENSION BETWEEN TWO FLUIDS BASED ON SPINNING DROP METHOD - Kisil, Igor; Barna, Olga; Kuchirka, Yuriy (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The spinning drop method foundations of measuring interface tension between two immiscible liquids are considered. Different techniques of the spinning drop method and their metrology evaluation are compared. The dimensionless parameters of spinning drop are calculated using the fourth-order Runge–Kutta procedure and they are approximated by the seventh-order polynomial dependence. The relative errors of the different techniques and the approximate dependence are obtained.